PERANCANGAN PROTOTYPE PEMBUKA PINTU BRANKAS MENGGUNAKAN SENSOR KETUK DAN FINGERPRINT BERBASIS ARDUINO - Rahmawati, Mega; Nopriadi, Nopriadi (LPPM Universitas Putera Batam, 2021)
Safe security systems generally use a manual security system, which is to open it by turning or pulling a lever and also using a secret code. This security system is a system that is less efficient in its use as security access, because it only has one level of security, so there is still the possibility that other people can crack passwords and break them or steal them. The aim of this research is to create a dual security system in a safe that is applicable and easy to use. The tools used in the manufacture of this tool are Arduino Uno, Piezobuzzer tap sensor, Fingerprint Sensor, solenoid, Adapter / Power supply, 1 ch Relay and jumper cables connected to pins on the network on the Arduino Uno. The work arrangement of this tool begins with providing a power supply to the electrical components after the component is active with the power supply, so the security system in the safe can be used. The next step used to open the safe is to give two taps accompanied by a pause in each tap right in the reading area of ​​the piezobuzzer tap sensor which is in the safe to activate the fingerprint sensor, after the fingerprint sensor is active or in a correct state, the fingerprint sensor will read and verify from the received fingerprint and the Relay 1ch will forward it as a command to Solenoid to open the brane door.